Agréguese al art. 297 de la ley de propiedad intelectual un inciso para que intervenga el instituto ecuatoriano de propiedad intelectual en el juicio verbal sumario de dicha materia - Toala León, Ilia Isabel (2016)
This thesis deals with the fact that the Instituto Ecuatoriano de Propiedad Intelectual (IEPI) currently not involved in verbal summary trials that subject though is the specialized state of Ecuador and elsewhere organism judges do not have the full knowledge of all that is intellectual property, not real justice is done, and that is not provided in the Ley de Propiedad Intelectual that judges should consult the Institute and obligatorily at least once before sentencing in verbal summary trials but that everything has been studied in the competent organ of the judiciary that is the District Court No. 1 Administrative headquarters Quito, in the 2015 period, carried out according to the provisions of Regulation Regime Academician of the National University of Loja . Raised the overall goal being added to Art. 297 of the Ley de Propiedad Intelectual a clause to intervene the Instituto Ecuatoriano de Propiedad Intelectual (IEPI) in verbal summary trial said specialty by consulting the competent judiciary City Quito DM, it is noteworthy about the importance of this reformatory norm in the legal and legitimate issue of the measures, including those statements. The methods used for the preparation of this research work were: the deductive method, inductive method, analytical methods - synthetic, comparative method, the same that were used to achieve the proposed goal efficiently. The techniques and instruments used were: a survey and an interview which applied to judges, the result of which found that legal reform is necessary and urgent in order for true justice emerged. In short, intervention in the IEPI is necessary for consultation once before sentencing, all with the aim to issue orders or a fault in law.